Rituales mortuorios y ceremonial cívico: José de San Martín en el panteón argentino - Bragoni, Beatriz (2013)
The nineteenth century in Spanish America exhibits a true saga of funeral ceremonies intended to exalt the role of great men in the configuration of the symbolic arsenal which contributed to molding the foundational mythology of nation-states. The Republican state language turned the association between hero, national body and posterity into a resource of the affirmation of national authority and social and political cohesion. Converted into keystones in the building of the national pantheon, State funerals carried out during the 19th century in the majority of the Spanish American republics became formidable instruments of political and cultural construction. Along these lines, the presen tarticle is occupied with contextualizing the slow process of placing José de San Martín as an Argentine national hero within the coordinates of 19th century European and Spanish American funerary rituals.